INDEPENDENT WORK OF STUDENTS IN STUDY PEDAGOGICAL DISCIPLINES IN HIGHER EDUCATION EDUCATIONAL INSTITUTIONS - L.O. Savchenko; N.I. Zelenkova (Academy of Cognitive and Natural Sciences, 2008)
The article is devoted to the problem of organization of students independents work. The independent work is considered as the way of teachers training.